2003
DOI: 10.1007/s00259-003-1142-0
|View full text |Cite
|
Sign up to set email alerts
|

Optimising conditions for radiolabelling of DOTA-peptides with 90Y, 111In and 177Lu at high specific activities

Abstract: DOTA-conjugated peptides, such as [DOTA(0),Tyr(3)]octreotide (DOTATOC) and [DOTA(0),Tyr(3)]octreotate (DOTA-tate), can be labelled with radionuclides such as (90)Y, (111)In and (177)Lu. These radiolabelled somatostatin analogues are used for peptide receptor radionuclide therapy (PRRT). Radioligands for PRRT require high specific activities. However, although these radionuclides are produced without addition of carrier, contaminants are introduced during production and as decay products. In this study, paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
125
0
19

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(147 citation statements)
references
References 11 publications
(11 reference statements)
3
125
0
19
Order By: Relevance
“…During irradiation, 177 Lu absorbs neutron and leads to the formation of 177/ 178 Hf, which results in the accumulation of the 177 / 178 Hf carrier in the target system. While the presence of 177/178 Hf(IV) has no consequences in the efficiency of 177 Lu(III)-labeling reactions [53], accumulation of hafnium atoms decreases the specific activity.…”
Section: Calculation Of Irradiation Yieldmentioning
confidence: 99%
See 3 more Smart Citations
“…During irradiation, 177 Lu absorbs neutron and leads to the formation of 177/ 178 Hf, which results in the accumulation of the 177 / 178 Hf carrier in the target system. While the presence of 177/178 Hf(IV) has no consequences in the efficiency of 177 Lu(III)-labeling reactions [53], accumulation of hafnium atoms decreases the specific activity.…”
Section: Calculation Of Irradiation Yieldmentioning
confidence: 99%
“…Under this premise, it is pertinent to note that owing to the long half-life and low neutron absorption cross section, the activity levels of 177m Lu formed will be low but still be of possible concern. Whereas the 177m Lu waste issue must be locally resolved, estimates have clearly shown that the resulting radiation dose increase from the presence of 177m Lu is insignificant at clinically significant dose levels, at least for PRRT [53]. Under the optimized production conditions, the reported values for the 177m Lu/ 177 Lu ratio vary between 0.01 %-0.02 % at EOB [57].…”
Section: Calculation Of Irradiation Yieldmentioning
confidence: 99%
See 2 more Smart Citations
“…We used benzyl-DTPA in a previous study because of the easy and quick labeling at room temperature. Some publications (27,28) suggest that the use of DOTA derivatives requires heating up to 100˚C for efficient indium labeling, and that labeling at lower temperatures is rather inefficient (29). On the other hand, the gallium-DTPA complex is not considered to be sufficiently stable in vivo (30), and the use of PET with 68 Ga-labeled Z HER2:342 for visualization of HER2 would require the use of a macrocyclic chelator.…”
Section: Introductionmentioning
confidence: 99%